Formação de biofilmes de Pseudomonas aeruginosa expostas a efluentes de laboratório didático multiusuário de saúde - Amaral, Débora Conceição da Silva (2024)
The formation of biofilms by Pseudomonas aeruginosa represents a significant concern due to its persistence and resistance to environmental factors. These biofilms not only confer adaptive advantages to the microorganism but also pose risks to public health and the environment, especially when originating from environments with a high stress load, such as laboratories. This study evaluated biofilm formation in isolates of Pseudomonas aeruginosa obtained from the sinks of multi-user didactic laboratories, which generate effluents with a high load of toxic substances. The isolates were quantified pyocyanin and susceptibility to antimicrobials. A solution containing residues of material manipulated in the sinks was prepared, and the isolates were tested for biofilm formation on different substrates and motility alteration. Twelve specimens were obtained, of which 11 were positive for Pseudomonas spp. and 4 confirmed as Pseudomonas aeruginosa (2A, 2B, 3A, and 3B), with two of them (2A and 3A) producing pyocyanin. All isolates were sensitive to cefoxitin, but isolate 3A stood out as the most resistant, including to cefepime. Preferential adhesion was observed on hydrophilic surfaces over hydrophobic ones, as well as alterations in motility. The 1% leachate was considered toxic to 100% of Artemia salina. These results highlight the high adaptability of Pseudomonas aeruginosa to environments with a high degree of environmental stress, providing important insights into the mechanisms of resistance and persistence of this pathogen in education laboratory settings, as well as raising an alert about the increasing resistance of fourthgeneration antibiotics in P. aeruginosa isolates.